The Effect of Comic Strips Media to The Writing Skills of The Eighth Grade Sudents’ of SMP Negeri 3 Pematangsiantar In Narrative Text - Harita, Indah Permata Sari; Napitupulu, Selviana; Sitanggang, Anita (Indonesian Research Journal on Education, 2024)
The aim of this research is to determine the effect of using comic strips media to the writing skills of eighth grade students of SMP Negeri 3 Pematangsiantar in narrative text 2024/2025 academic year. The research aimed to determine the effect of using Comic Strips Teaching media as generic structure in narrative text at eighth grade of SMP Negeri 4 Pematangsiantar. The objective of the study was to find out whether this media could significantly improve students' writing skills in narrative text. The research utilized a quantitative approach with a quasi-experimental design, which included both a pre-test and post-test. The population consisted of 330 students, from which two classes were selected via cluster purposive sampling. The experimental group received instruction using comic strips teaching media, while the control group used youtube teaching media. Data collection involved administering pre-tests and post-tests to both the experimental and control groups. Findings showed that the students in the experimental group achieved significantly higher post-test scores compared to the control group, indicating that the comic strips teaching media to the writing skills in narrative text. It can be proven by the following result: The degree of freedom (df) is 58 and the t-table at the level of significant 5% for a two-tailed test is 1,315. The researcher found the pre- test score of experimental (Ma) was 67,13, which increased to 78 in the post-test. Then pre-test mean score of control class, was 69,03 and went up 75,4. It meant that using the guided story pyramid strategy had a greater effect than the conventional strategy. After calculating the data from the preceding point, the researcher discovered that the testing hypothesis shows the t-test (4,591) is higher than the t-table (1,315). Alternative Hypothesis (Ha) is accepted, and Null Hypothesis (H0) is rejected. As a result, it is possible to conclude that using Comic strips teaching media has an effect on students’ ability in writing narrative text at grade VIII SMP Negeri 3 Pematangsiantar.